An Exploration On The Use Of Podcast In Speaking Class - Agustina Lestary (ENLIT, 2021)
The objective of this study is to describe the use of podcast in a speaking classroom. This study is also intended to elaborate students’ perspective while using podcast. It is expected that the result of this study will provide a better insight towards students’ point of view regarding speaking in general and the use podcast in specific. This study is a descriptive study with a qualitative approach. The subjects of this study are students at STKIP PGRI Banjarmasin who are taking Academic Speaking course. The students are required to broadcast podcasts throughout the course and fill in a questionnaire at the end of the semester. The use of podcast will be explained and the response of the questionnaire will be analyzed. The result of this study shows that students find podcast is a helpful activity to help them with their speaking practice. The fact that podcast reduce the direct contact to the audience helps the students to reduce their anxiety and boost their confidence. By the end of the day, the students find it is quite comfortable to speak in English through podcast.